The Mosaic Seeing or Inadequate Optics? (reflections about the all-Ukrainian conference «American Philosophy of Education from the Ukrainian Researchers Point of View») - Plakhotnik, Olga (Filosofiya osvity. Philosophy of Education, 2006)
This paper considers how Ukrainian researchers have understood and evaluated the American philosophy of education’s phenomenon — according to the materials of all-Ukrainian conference on 22nd of December, 2005 in Poltava. The topicality of this field of philosophy of education’s research is proved, the features of approaches to analysis of the strong and weak points of American education are determined and philosophically discussed.